2018
DOI: 10.2176/nmc.oa.2017-0198
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hyperthyroidism and Thyroid Autoantibodies with Moyamoya Disease and Its Stroke Event: A Population-based Case-control Study and Meta-analysis

Abstract: The aim of this study was to investigate the specific thyroid condition and thyroid autoantibodies in adult moyamoya disease (MMD) according to clinical presentation (ischemia vs. hemorrhage stroke). In addition, a meta-analysis was performed to reveal the association between adult MMD and elevated thyroid function, or autoantibodies. Prospectively collected data on 169 consecutive patients with MMD at a single institution were analyzed. Community-based controls matched for age and sex were selected for compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…HLA-DRB1*04 : 10 -positive patients account for ~10% of Japanese MMD patients; therefore, its involvement should be investigated in a larger population or other institutions. In addition, association between thyroid dysfunction and MMD is different between Asians and Caucasians: GD is more prevalent among Japanese MMD patients, whereas HT is more prevalent among Caucasian MMD patients [510]. The patients and controls in this study were residents of Tohoku and Kanto districts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HLA-DRB1*04 : 10 -positive patients account for ~10% of Japanese MMD patients; therefore, its involvement should be investigated in a larger population or other institutions. In addition, association between thyroid dysfunction and MMD is different between Asians and Caucasians: GD is more prevalent among Japanese MMD patients, whereas HT is more prevalent among Caucasian MMD patients [510]. The patients and controls in this study were residents of Tohoku and Kanto districts.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is expected to unveil the pathogenesis of MMD and diagnose MMD before onset of stroke. Although the etiology of MMD remains undetermined, previous studies showed an association between autoimmunity and MMD [411], such as the high frequencies of thyroid dysfunction and type 1 diabetes among MMD patients [410].…”
Section: Introductionmentioning
confidence: 99%
“… 10 Thyrotoxicosis will also aggravate the ischemic situation in MMD. 11 The underlying reason for this is unknown, but several pathological mechanisms have been proposed. First, thyrotoxicosis tends to induce hypermetabolism and increases oxygen consumption in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with MMD but without GD, elevation of thyroid autoantibodies is frequently encountered; additionally, thyrotoxicosis can worsen the ischemic condition of MMD. 10 , 11 This indicates a complicated interaction between GD and MMD.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between specific thyroid condition and moyamoya disease has been reported for some time, and it has also been reported to be related to clinical manifestation. Specifically, hyperthyroidism and elevated anti-thyroperoxidase antibody are likely to be associated with ischemic stroke in adult moyamoya disease [30].…”
Section: Clinical Factors Associated With Ischemic Onset Moyamoya Diseasementioning
confidence: 99%